A Paracas offering in Cerro del Gentil, middle valley of Chincha - Tantaleán, Henry (2020)
This paper describes the finding of an extraordinary offering deposited in the final layers of ritual entombment of the sunken patio of the main Paracas building in Cerro del Gentil, located in the mid-valley of Chincha, peruvian southern coast. Because to its excellent state of preservation and the high quality of the elements that constituting this offering, it allows us to delve into the ritual practices developed in the context of an activity of utmost importance to the users of the Cerro del Gentil building just prior to its abandonment during the III century before Christ.